The Correlation Between Family Economic Social With The Result Of Study Social At Students Class VIII Academic Year 2012/2013 Of SMP Pertiwi 2 Padang - Suherman, Robbi; Ahmad, Ridwan; Yuherman, Yuherman (Pendidikan Geografi, 2013)
This research aims to tested (1) the correlation between parents education with result of study social at students class VIII of SMP Pertiwi 2 Padang, (2) The correlation between parents income with result of study social at students class VIII of SMP Pertiwi 2 Padang. (3) The correlation between parents attention with result of study social at students class VIII at SMP Pertiwi 2 Padang.Kind of research used is correlation descriptive. Populations in this research are students class VIII of SMP Pertiwi 2 Padang which number in 85 students. Respondent sample take over with total sampling/surfeited sampling, technique. Data collected with propagating questioner to respondent. An analysis data technique used are double correlation and double regress.Based on result of correlation analysis and regress, hence got the result of the following : (1) There are no significant relation between parents level education with result of study social at students class VIII of SMP Pertiwi 2 Padang because t count < t table (-0,340 > 1,99006),strength including very low (r = 0,038 )and contribution given the including is very small (0,14%), (2) There are significant relation between parents income with result of study social at students class VIII of SMP Pertiwi 2 Padang because t countsÂ  > t table; (2,512 >1,99006).Strength in clouding low (r= 0,267 ) and contribution given the including is very small (7,13%), (3) There are significant relation between parents attention with result of study social at students class VIII of SMP Pertiwi 2 Padang because t counts > t table, (0,217) and contribution given the including is very small (4,71%), (4) There are significant relation between parents attention as together toward result of study social at students class VIII at SMP Pertiwi 2 Padang because f counts > Â f table (3,896 > 2,72), Strength of relation between both variable to ward Y variable including low (r= 0,375) and contribution given the including is very small (12,7%).